Navigating phenylketonuria management to improve it in Latin America: a systematic literature review and applicability analysis - Aguirre, Alex S.; Haro, Edison; Campodónico, Alberto; Mendoza, Alissa; Bahamonde, Bernarda; Romero, Vanessa I. (Frontiers in Nutrition, 2024)
Introduction: Phenylketonuria (PKU) is an autosomal recessive metabolic disorder resulting from phenylalanine hydroxylase deficiency, which impacts neurodevelopment. Lifelong low-phenylalanine diets and multidisciplinary care are pivotal for managing PKU. Latin American challenges in PKU care include diverse newborn screening programs, limited specialized healthcare, and resource scarcity.Methods: A systematic literature review was conducted (2010-2023) on PKU management following PRISMA guidelines. Inclusion criteria encompassed English/Spanish articles focusing on PKU management guidelines approved by an organization as well as articles focusing on PKU management in Latin America. After screening 127,276 results, 6 articles were included.Results: Six articles were analyzed, highlighting shared principles like multidisciplinary care, lifelong dietary adherence, personalized plans, and regular monitoring. Guides emphasized regional variations, breastfeeding complexities, and challenges for pregnant women with PKU.Discussion: Multidisciplinary care emerges as critical, incorporating physicians, psychologists, dietitians, nurses, and genetic counselors. Lifelong adherence to low-phenylalanine diets and personalized strategies for different life stages are emphasized. Challenges in Latin America include healthcare gaps, scarce resources, and reliance on international guidance. The importance of breastfeeding, preconception care, and comprehensive support for pregnant women with PKU is underscored.Collaborative efforts are essential to address PKU challenges in Latin America. Advocacy for awareness, specialized training, regional databases, and international collaborations can enhance diagnosis and management, ensuring a better quality of life for PKU individuals in the region. Embracing lessons from existing guides will contribute to improved PKU care and overall well-being.